New insights in understanding biliary atresia from the perspectives on maternal microchimerism - Muraji, Toshihiro; Masuya, Ryuta; Harumatsu, Toshio; Kawano, Takafumi; Muto, Mitsuru; Ieiri, Satoshi (Frontiers in Pediatrics, 2022)
Biliary atresia (BA) is a fibroinflammatory cholangiopathy and portal venopathy. It is of unknown etiology and is associated with systemic immune dysregulation, in which the first insult begins before birth. Maternal microchimerism is a naturally occurring phenomenon during fetal life in which maternal alloantigens promote the development of tolerogenic fetal regulatory T-cells in utero. However, maternal cells may alter the fetus’s response to self-antigens and trigger an autoimmune response under certain histocompatibility combinations between the mother and the fetus. A recent report on a set of dizygotic discordant twins with BA, one of whose placentae showed villitis of unknown etiology, implies a certain immune-mediated conflict between the fetus with BA and the mother. Maternal chimeric cells persist postnatally for various time spans and can cause cholangitis, which ultimately leads to liver failure. In contrast, patients who eliminate maternal chimeric cells may retain their liver function.